The Relationship of Health Service Quality With Inpatient Satisfaction At Santa Elisabeth Hospital Medan - Sigalingging , Vina Yolanda Sari; Saragih , Ice Septriani; Sihaloho, Fanny Meylita (Jurnal EduHealth, 2022)
Patient satisfaction is a condition where patient expectations are met through the speed of response from officers and the provision of good quality services. So it can be understood that to provide a sense of satisfaction to patients need extra effort in making it happen. The quality of health services is a form of consumer assessment of the level of service received with the level of service expected. This study aims to determine the relationship between the quality of health services and the satisfaction of inpatients at the Santa Elisabeth Hospital, Medan in 2022. This study used the Cross Sectional Study method. By using The sampling technique used was accidental sampling , which consisted of 64 respondents. The research instrument used a Health Service Quality and Inpatient Satisfaction Questionnaire at Santa Elisabeth Hospital Medan. The results showed that the service quality was not good and it was less satisfied by 64.1.0% with a total of 41 respondents. Patients with good service quality and satisfied are 40.6% with a total of 26 respondents. Statistical test showed p-value of 0.004. This means that there is a relationship between the quality of health services and patient satisfaction in the Inpatient Room of Santa Elisabet Hospital Medan in 2022 with a close correlation of r = 0.354, therefore the quality of health services needs to be considered and applied to increase inpatient satisfaction at Santa's Hospital. Eisabeth Medan